Critical Race Pedagogy for More Effective and Inclusive World Language Teaching - Anya, Uju (Applied linguistics, 2021)
Abstract To address racial inequity and the exclusion of African Americans in applied linguistics, second-language acquisition, and world language (WL) education, our field must reckon with social justice problems of racism and anti-Blackness. Theoretical frameworks of critical race theory (CRT) and critical race pedagogy (CRP) elucidate how such injustices are perpetuated, plus, propose solutions for them. This article discusses racism and anti-Blackness in WL curriculum, materials, and instructional practices. It presents a post-hoc CRT analysis of findings from two studies: (i) an ethnographic study examining Spanish curriculum and instructional practices at two minority serving postsecondary institutions and (ii) a participatory action research collaboration with Spanish instructors examining curriculum at a predominantly white institution—both studies linked by how they reveal endemic racism and anti-Blackness in WL programmes. Ultimately, this article addresses how African Americans can more authentically and successfully participate in WL programmes. It introduces to the field a proposal of CRP for more effective WL teaching to promote practices in antiracism, equity-mindedness, and inclusivity for greater retention and success of Black students.